CRP levels and platelet count as markers of prognostic index in COVID-19 patients (Panacea Journal of Medical Sciences, 2025)
Background: Diagnostic tests like complete blood count (CBC) and C-reactive protein (CRP) are pivotal in diagnosing COVID-19 and assessing treatment outcomes. The presence of hyper coagulability and disseminated intravascular coagulation in COVID-19 patients correlates with diminished platelet counts.Materials and Methods: A cross-sectional analytical observational study was conducted on 150 individuals diagnosed with COVID-19 between January 2022 and April 2022, utilizing data sourced from Dr. K.K.B.M. Subharti Hospital Dehradun. The study specifically targeted COVID-19 patients below 60 years old with confirmed RT-PCR test results. Medical records were scrutinized for laboratory findings regarding platelet count and CRP levels at the mentioned hospital. CRP levels were determined using the Turbidimetric method, while CBC was performed using Electrical Resistance Detection. Platelet isolation was achieved by rotating a blood sample in the Nihon Kohden Celltac alpha machine followed by microscopic examination. Data analysis was conducted using SPSS statistical software version 20.0 provided by IBM Corp.Results: A direct correlation between CRP concentrations and the COVID-19 severity was observed.(p<0.001) Platelet counts demonstrated a significant negative correlation with CRP levels (r = -0.491**, p < 0.01). This inverse relationship suggests a potential compensatory mechanism whereby platelets modulate inflammation and coagulation.Conclusion: We concluded that Platelet count and CRP levels serve as crucial prognostic markers for determination of covid severity and for clinicians managing COVID-19 cases.